2021
DOI: 10.2139/ssrn.3810765
|View full text |Cite
|
Sign up to set email alerts
|

Remote Triage Incorporating Symptom-Based Risk Stratification for Suspected Head and Neck Cancer Referrals: A Prospective Population-Based Study

Abstract: Remote triage incorporating symptom-based risk stratification for suspected head and neck cancer referrals: A prospective population-based study. Cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
(20 reference statements)
2
17
0
Order By: Relevance
“…Indeed, Hardman et al demonstrated that the negative predictive value of a "low risk" outcome from the calculator was 99.1% in data from over 4500 patients triaged during the initial COVID19 surge. 14 Our results were in keeping with this finding, with cancer conversion rates of 17% and <1%, respectively, for the highand low-risk pathways. The patients at our center identified as highrisk were essentially managed as they would have been prior to the pandemic; that is they are reviewed in a face to face clinic for clinical examination including fiberoptic nasendoscopy.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, Hardman et al demonstrated that the negative predictive value of a "low risk" outcome from the calculator was 99.1% in data from over 4500 patients triaged during the initial COVID19 surge. 14 Our results were in keeping with this finding, with cancer conversion rates of 17% and <1%, respectively, for the highand low-risk pathways. The patients at our center identified as highrisk were essentially managed as they would have been prior to the pandemic; that is they are reviewed in a face to face clinic for clinical examination including fiberoptic nasendoscopy.…”
Section: Discussionsupporting
confidence: 89%
“…Telephone consultations have also been employed effectively when triaging two-week-wait suspected head and neck cancer referrals. Hardman et al showed that use of a validated risk calculator, utilised as part of a telephone consultation, demonstrated a low risk of harm, with potential to reduce the number of unnecessary hospital attendances 3 .…”
Section: Discussionmentioning
confidence: 99%
“…HNSCCUP is a condition where the patient presents with metastatic cancer in the lymph nodes of the neck but where the original site of the cancer (which is usually thought to be from the mucosa lining the upper aerodigestive tract) cannot be identified on clinical examination, imaging investigations or diagnostic biopsies. 4 It accounts for roughly 3-5% of head and neck cancers, which itself is the 8th most common form of cancer in the UK [14][15][16].…”
Section: Introductionmentioning
confidence: 99%